(untitled) (International Journal of Irrigation and Water Management, 2020)
The aim of our survey was to assess the effect of irrigation water of the microbiological quality on the production chain of lettuce in the Dakar area. Microbiological analysis showed that 35% of irrigation water was contaminated by Salmonella spp. between the two water-types used for irrigation (groundwater and wastewater), no significant difference (p>0.05) in their degree of contamination was found. The incidence of different types of irrigation water on the contamination rate of lettuces from the farm (Pikine and Patte d’Oie) was not different either (p>0.05). However, the contamination rate of lettuce from markets of Dalifort and Grand Yoff that were supplied by the area of Patte d’Oie was greater than those of Sham and Zinc supplied by Pikine (p<0.05). Comparison of serotypes of Salmonella isolated from irrigation water and lettuce showed that irrigation water may affect the microbiological quality of lettuce. Manures, frequently used as organic amendment in cultivating lettuce are another potential source of contamination. These results showed that lettuce may constitute effective vectors for the transmission of pathogens to consumers. Extensive treatment of the used wastewater and/or composting of manure could considerably reduce these risks.